The optimal rate of government spending on economic growth in Libya during the period (2000-2020) - Ertimi باسم (Journal of Pure & Applied Sciences, 2022)
This study aimed to analyse the efficiency of government expenditure in Libya and what is the optimal limit of government expenditure during the period 2000 –2020 using the developed model of "Scully", and the econometric approach based on the Fully Modified Ordinary Least Squares method (FMOLS). The study came to several conclusions, the most notable of which are: The optimal size of government expenditure as a percentage of GDP in Libya is estimated to be 34% during the study period, while the average during the period is 69%, which is higher than the percentage of optimal government expenditure, indicating that public spending in Libya is inefficient and does not contribute to improving economic growth rates. To achieve economic growth, the research advocated a strategy of spending reduction and the implementation of several economic strategies other than increasing government spending.